2012
DOI: 10.1029/2011jc007246
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal thermocline in the China Seas and northwestern Pacific Ocean

Abstract: .[1] Climatological seasonal variations of the thermocline in the China Seas and northwestern Pacific Ocean were studied using historical data from 1930 through 2001 (707,624 profiles). The quantitative roles of surface thermal buoyancy (B q ), haline buoyancy flux (B p ), and total buoyancy flux (B) against the wind-induced mixing (t) in different seasons and regions were also explored using the buoyancy ratio (R = |B q /B p |) and the Monin-Obukhov depth ratio (d), respectively. The thermocline has obvious … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
52
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 29 publications
0
52
0
1
Order By: Relevance
“…However, there is no objective way to determine the criterion, which ranges from 0.05uC m 21 to 2uC m 21 (Coloso et al 2011;Hao et al 2012). For example, the criterion value of 0.05uC m 21 is used for the Chinese shelf (.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is no objective way to determine the criterion, which ranges from 0.05uC m 21 to 2uC m 21 (Coloso et al 2011;Hao et al 2012). For example, the criterion value of 0.05uC m 21 is used for the Chinese shelf (.…”
Section: Methodsmentioning
confidence: 99%
“…For example, the criterion value of 0.05uC m 21 is used for the Chinese shelf (. 200 m; Zou et al 2001), 0.2uC m 21 is used for the Chinese shelf (# 200 m; Hao et al 2012), and 1uC m 21 is used in Canadian Shield lakes (Fee et al 1996).…”
Section: Methodsmentioning
confidence: 99%
“…6, 1019-1032, December 2017 general categories: (1) fixed temperature difference (FTD) methods -the depth at which the potential temperature, θ, has decreased by a prescribed amount relative to a reference depth, preferably the sea surface; (2) fixed density difference (FDD) methods -the depth at which the potential density, σ θ , has increased by a prescribed amount relative to a reference depth, again preferably the sea surface; (3) fixed temperature gradient (FTG) methods -the depth at which the gradient in θ with depth z, δθ/δz, has increased to a prescribed value; and (4) fixed density gradient (FDG) method -the depth at which the gradient in σ θ with depth, δσ θ /δz, has risen to a prescribed value. The prescribed values that have been used varied, for example, a drop in θ of 0.2 (Thompson 1976), 0.5 (Price et al 1986;Kelly and Qiu 1995;Obata et al 1996;Monterey and Levitus 1997), 0.8 (Kara et al 2000;Qu et al 2007) or even 1.0°C (Lamb 1984;Wagner 1996), an increase in σ θ of 0.125 or 0.13 σ θ unit (Miller 1976;Levitus 1982;Spall 1991;Huang and Russell 1994), an increase in -δθ/δz to 0.05°C m -1 (Qu 2001;Hao et al 2012) and an increase in δσ θ /δz to 0.01 (Lukas and Lindstrom 1991), 0.05 (Tseng et al 2007) or 0.1 σ θ unit m -1 (Tseng et al 2005;Wong et al 2007a, b) in the FTD, FDD, FTG, and FDG methods, respectively. The reference depths used include the sea surface (Miller 1976;Thompson 1976;Levitus 1982;Lamb 1984;Price et al 1986;Spall 1991;Huang and Russell 1994;Kelly and Qiu 1995;Obata et al 1996;Wagner 1996;Monterey and Levitus 1997) and 10 m below the sea surface …”
Section: Introductionmentioning
confidence: 99%
“…As a result, MLD generally tends to decrease with decreasing latitude, and, the seasonal variations in MLD in the tropical waters tend to be smaller (Monterey and Levitus 1997;Montégut et al 2004). As a part of several studies for diverse purposes, the MLD in the tropical northern South China Sea (SCS) has been estimated by various investigators using a variety of different methods: a FTD method with a drop in θ of 0.8°C relative to that at 10 m (Qu et al 2007); a FTG method at a temperature gradient of 0.05°C m -1 (Qu 2001;Ge et al 2003;Hao et al 2012); a FDG method at density gradients of 0.05 (Tseng et al 2007) or 0.1 σ θ unit/m (Tseng et al 2005(Tseng et al , 2009Wong et al 2007b). Wong et al (2007b) reported that, unlike what is expected in tropical waters, the MLD in the northern SCS varies over a relatively wide range seasonally, from 20 m in the summer to 90 m in the winter.…”
Section: Introductionmentioning
confidence: 99%
“…We collected 7 random points in the model from north part to south part to see the vertical profiles and compared them between La Niña, El Niño, and normal scenario. Thus thermocline layer calculate using gradient criterion 0.05 o C/m to determine the depth of upper and lower threshold of thermocline layer [22].…”
Section: Atmospheric Forcingmentioning
confidence: 99%